Criminological Juridical Review of Traffic Accidents Resulting in Child Deaths Due to Negligence Reviewed from the Perspective of the Juvenile Justice System - Dian - Rahadian; Farida - Kaplele (Faculty of Law, Universitas Pekalongan, 2022)
The aim of the normative research currently being carried out is to find out how criminologically the occurrence of traffic accidents carried out by children occurs due to negligence or carelessness in driving motorized vehicles. This implementation is regulated in Law Number 22 of 2019 concerning Road Traffic and Transportation as well as the Juvenile Criminal Justice System Law. The research method used is descriptive analysis which leads to normative juridical legal research, namely research carried out by referring to legal norms, namely researching library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results of the research show that in the Juvenile Justice System and related to Criminological Science, it is clear that the Juvenile Criminal Justice System Law regulates basic and additional criminal penalties. In relation to the issue of responsibility for a child who is still a minor, this concerns matters of age where he can be held accountable but which are outside the Criminal Code.